PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DENGAN PENDEKATAN SAINTIFIK - Muhammad Ali P; Hamzah Upu; Djadir Djadir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
The purpose of this research to develop learning tools are valid, practical and effective to use the type cooperative model of student teams achievement divisions (STAD) with a scientific approach to the subject of linear equations in one variable class VII SMP Negeri 1 Polewali. The results of this study indicate the development of learning tools using model 4-D, Irish learning developed first validated by two experts before conducting two trials, the test device is first learning to do in SMP Negeri 2 Polewali followed by 25 students, and did repair device after the first trial consulted validator, devices produced in tested again in a different school in SMP Negeri 1 Polewali called second trial which was followed by 25 students. Devices in the tested reversible and consult validator to produce learning tools are valid, the learning device performing well at the time of trial, and achievement test has tercapi classical completeness, student activities are consistent with the expected students to give a positive response of the device so that the power of learning is said to be practical and effective. The resulting devices distributed or disseminated on a limited basis through a consultative meeting Subject Teachers (MGMPs) Mathematics Polewali Mandar.